The Second Kiss dan GPR54: Amplifikasi dan Sekuensing Gen Penyandi Faktor Reproduksi Ikan Nila (Oreochromis niloticus) - Ricky Febrinaldy Simanjuntak (Fakultas Perikanan Dan Ilmu Kelautan Universitas Borneo Tarakan, 2017)
Several years ago since it was first found to play a role in metastasis, Kisspeptin (encoded by Kiss1) that has GPR54 cognitive receptors is known to act as a regulator to initiating reproductive factors, involving GnRH secretion in some vertebrates, including fish. However, each of the other vertebrates will express different kinds of Kisspeptin based on the types and its evolutionary line. The aims of this research is to confirm the Kiss2 type along with the GPR54 receptor on Tilapia. RNA isolation, cDNA cloning and DNA amplification was made from samples of tilapia testes. The DNA amplification result will then be sequenced by MACROGEN. Inc. The amplified results of the Kiss2, GPR54 and β-Actin (positive control) genes observed using agarose gel electrophoresis show the product size of each gene is 199 bp, 155 bp and 197 bp. Confirmation of sequencing results by the BLAST method for Kiss2, GPR54 and β-Actin genes were: 100%, 97% and 100%, respectively. Based on the research, it can be concluded that the results of each target isolated from the gonad of tilapia indicate the homology/similarity of the sample of each target nucleotide sequence with the world database sequence (gene bank).Keywords: Kiss2, GPR54, Reproduction, Nile Tilapia